PROGNOSTIV VALUE OF TISSUE LOCALIZATION OF IMMUNOGLUBULIN A IN MUCINOUS AND SEROUS OVARIAN TUMORS - Milosavljević, Zoran; Tomić, Ljiljana; Malić, Živka; Milovanović, Brankica (ACADEMIC REVIEW, 2018)
Study was designed to reveal the prognostic significance of IgA and mucin secretion in ovarian neoplasms. Samples of ovarian tumours of 34 female patients were routinely processed and stained with anti-IgA antibody as well as with histochemistry methods for mucin verification. In our study mucin type and tissue immnulocalization of the IgA was proven to be a good prognostic tool of the degree of the cellular atypia. High immunoglobulin A expression was verified in the epithelium and along the luminal border of well differentiated tumors. Histochemical mucin analysis showed quantitative and qualitative changes in mucin secretion that corelates with the degree of tumor differentiation. IgA and change of epithelial mucins are valid prognostic factors in ovarian neoplasms.